Salmonella serovars in laying hen flocks and commercial table eggs from a region of Sao Paulo State, Brazil - Freitas Neto, O. C. de [UNESP] (2014)
Salmonella spp. is the main originator of human foodborne diseases worldwide and is mainly transmitted by food containing eggs. In Brazil, as a result of the lack of studies and data collection very little is known about the prevalence of Salmonella spp. in laying hen flocks and commercial table eggs. Consequently the present study was elaborated and aimed at generating data about Salmonella spp. in part of the Brazilian egg production chain. Eight flocks of day-old chicks, eight flocks of adult laying hens (four vaccinated with bacterin against Salmonella Enteritidis and four unvaccinated) and commercial table eggs from four supermarkets were examined. Salmonella spp. was isolated in 50 % of the newly hatched chicks, 25 % of the adult flocks and 1.5 % of egg samples examined. S. enterica subsp. enterica 4,12:r:-, S. Mbandaka, S. enterica subsp. enterica 6,7: z10:-, S. Enteritidis and S. Havana were the serovars isolated in birds. In commercial table-eggs S. Mbandaka, S. enterica subsp. enterica 6,7: z10:- and S. Braenderup were isolated. These results show that Salmonella spp. is present in laying hen flocks and consequently in eggs destined for human consumption. Probably, some of the Salmonella serovars are being introduced in egg farms by vertical via.